Diagnostic accuracy and clinical outcomes associated with prenatal diagnosis of fetal absent cavum septi pellucidi. (15th April 2018) - Pilliod, Rachel A.; Pettersson, David R.; Gibson, Thomas; Gievers, Ladawna; Kim, Amanda; Sohaey, Roya; Oh, Karen Y.; Shaffer, Brian L.
Abstract: Background: Absence of the cavum septi pellucidi (CSP) on prenatal imaging is historically associated with additional anomalies; however, recent cases of isolated absent CSP have also been identified. This study seeks to assess the accuracy of prenatal imaging in evaluating isolated absent CSP and to describe the spectrum of clinical outcomes. Methods: This is a retrospective observational study of all prenatally diagnosed absent CSP cases between 2011 and 2016 at our institution. Cases with additional structural parenchymal abnormalities were excluded. Clinical outcomes were abstracted from available records. Results: We identified 15 cases of prenatally diagnosed isolated absent CSP. All patients were initially diagnosed on ultrasound (US) and 11/15 patients had fetal magnetic resonance imaging (MRI) confirming the diagnosis. Prenatal US and MRI were concordant in all cases. Of the continuing pregnancies, 2 neonatal deaths occurred related to extreme prematurity. Two cases of septo‐optic dysplasia were identified in our cohort. Discussion: In this study, fetal MRI and US had a high degree of accuracy with concordant postnatal imaging. Our study is similar to other case series suggesting that a range of clinical outcomes is possible with isolated absent CSP, but long‐term patient follow up is necessary. Abstract : What's already known about this topic? Prenatally diagnosed absent cavum septi pellucidi (CSP) can be an isolated finding, or it may be associated with a spectrum of abnormal clinical outcomes. In the absence of other anomalies, patients with absent CSP have been reported to have normal development as well as severe septo‐optic dysplasia, though currently, these are the only 2 published reports to inform those counseling families about the clinical outcomes of prenatally suspected absent CSP. What does this study add? This study provides additional cases of prenatally diagnosed absent CSP to help further inform providers and patients about the possible outcomes and complications associated with absent CSP. Additionally, we believe this study is the first to examine the accuracy of prenatal imaging by ultrasound and MRI compared with postnatal imaging.